2020
DOI: 10.1111/jfbc.13538
|View full text |Cite
|
Sign up to set email alerts
|

Hub genes and sub‐networks of stoma‐related genes in Hylocereus undatus through trypsin treatment during storage revealed by transcriptomic analysis

Abstract: Hylocereus undatus, is a species of Cactaceae (Fan et al., 2014). Because of its high economic value, it has become a widely concerned fruit of emerging economy in recent years. The pitaya fruit is easy to rot after picking, and the fresh fruit supply period is short, so it is a good research material for fruit preservation (Freitas & Mitcham, 2013). At the later stage of storage, the metabolism of Reactive oxygen species (ROS) in fruit was unbalanced, and the accumulation of ROS in fruit and vegetables caused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The samples of the trypsin group and control group stored for 1 week were taken for transcriptome sequencing. All process flows are carried out according to the reports of Xia et al (2017) and us (Li, Li, et al, 2021; Pang et al, 2021). The transcriptome was subjected to differential expression analysis using DESeq2 software with default parameters to find DEGs between two samples using a strict algorithm: |log 2 FC| > = 1 & p ‐adjust .05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The samples of the trypsin group and control group stored for 1 week were taken for transcriptome sequencing. All process flows are carried out according to the reports of Xia et al (2017) and us (Li, Li, et al, 2021; Pang et al, 2021). The transcriptome was subjected to differential expression analysis using DESeq2 software with default parameters to find DEGs between two samples using a strict algorithm: |log 2 FC| > = 1 & p ‐adjust .05.…”
Section: Methodsmentioning
confidence: 99%
“…Our laboratory found that trypsin has a good fresh‐keeping effect on H. undatus . It can regulate the level of endogenous reactive oxygen species (ROS) in H. undatus peels (Li et al, 2019, 2020; Pang et al, 2020) and inhibit the level of saturated fatty acids (Li et al, 2022; Pang et al, 2022), induce the stoma closure (Li, Li, et al, 2021), and the biosynthesis of related substances in phenylpropanoid pathways such as lignin, chlorogenic acid (Li, Zhang, et al, 2021), and flavonoids (Pang et al, 2021). It can also affect the free radical scavenging activity of flavonoids, such as DPPH and ABTS (Li et al, 2014, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…This gene can be targeted for genetic modifications to create a guava cultivar with good keeping quality. During storage of dragon fruits, superoxide scavengers such as trypsin have been shown to delay fruit ripening by influencing genes involved in the flavanoid pathway [ 176 ], antioxidant signal pathways [ 177 , 178 ], redox enzymes [ 179 ] and stoma closure [ 180 ], with catechin gallate being the significant metabolite regulated by the treatment. After harvest, durian fruits undergo softening and dehiscence occurs in the peel.…”
Section: Shelf Lifementioning
confidence: 99%